The Influence of Distance and Level of Service Provision on Antenatal Care Use in Rural Zambia - Kyei, Nicholas N. A. (Public Library of Science, 2012)
BACKGROUND: Antenatal care (ANC) presents important opportunities to reach women with crucial interventions. Studies on determinants of ANC use often focus on household and individual factors; few investigate the role of health service factors, partly due to lack of appropriate data. We assessed how distance to facilities and level of service provision at ANC facilities in Zambia influenced the number and timing of ANC visits and the quality of care received. METHODS AND FINDINGS: Using the 2005 Zambian national Health Facility Census, we classified ANC facilities according to the level of service provision. In a geographic information system, we linked the facility information to household data from the 2007 DHS to calculate straight-line distances. We performed multivariable multilevel logistic regression on 2405 rural births to investigate the influence of distance to care and of level of provision on three aspects of ANC use: attendance of at least four visits, visit in first trimester and receipt of quality ANC (4+ visits with skilled health worker and 8+ interventions). We found no effect of distance on timing of ANC or number of visits, and better level of provision at the closest facility was not associated with either earlier ANC attendance or higher number of visits. However, there was a strong influence of both distance to a facility, and level of provision at the closest ANC facility on the quality of ANC received; for each 10 km increase in distance, the odds of women receiving good quality ANC decreased by a quarter, while each increase in the level of provision category of the closest facility was associated with a 54% increase in the odds of receiving good quality ANC. CONCLUSIONS: To improve ANC quality received by mothers, efforts should focus on improving the level of services provided at ANC facilities and their accessibility.